Online Self-Healing Scheme of Distribution Network Based on Mixed Integer Linear Programming - Tiecheng LI; Weiming ZHANG; Qian ZANG; Xianzhi WANG; Jiangbo REN; Kun ZHOU (Zhongguo dianli)
The existing distribution network self-healing schemes cannot meet the online requirements. In this regard, an online distribution network self-healing scheme based on mixed integer linear programming is proposed. First, we build a centralized 5G communication network architecture to solve the communication obstacles implemented by the self-healing solution. Secondly, a fault location model and a power supply recovery model based on mixed integer linear programming are respectively constructed to effectively solve the problem that the self-healing calculation time is too long when the scale of the distribution network is large. Finally, the fault location and power supply restoration are integrated into a self-healing model. After a fault occurs, only one self-healing operation is required to issue fault isolation and power supply restoration commands at the same time. The distribution network example shows that the solution speed of the fault location model and power supply recovery model based on mixed integer linear programming is significantly improved. Under the proposed 5G communication architecture, the proposed distribution network self-healing scheme can meet the online self-healing requirements.